DETERMINATION OF PHYLOGENlETIC ALLIES IN SOME SPECIES OF CROCUS IN IRAN THROUGH THE STUDY OF SOLUBLE PROTEINS, PEROXIDASES AND POLYPHENOL OXUDASES (Journal of Sciences, Islamic Republic of Iran)
The taxonomic affinity of six species of Crocus (C, cancellatus subsp. Damascenus C. almehensis, C. gilanicus, C. sativus, C.pallassi subsp. haussknechtii,C. speciosus subsp. speciosus) from Iran were studied usingdifferent electrophoresis techniques. The similarity index of the species was computed by comparison of protein bands of - Corm and seed tissues, and the related dendrogms of affinity dies were drawn. The local populations of C. cancellatus constitute the first cluster of dendrogram and along with autumnal species form a common cluster. C. almehensis, which in contrast to other species is vernal, joined them at a farther distance